THE DEVELOPMENT OF EDUCATIONAL ADMINISTRATIVE AND MANAGING MODEL FORDEVELOPMENT OF THE INNOVATION OF LEARNERS IN DIGITAL PERIOD FOR PRIVATE INSTITUTIONS OF UDON THANI PROVINCE - Meerakar, Amnuai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The article with the objectives included a study of fundamental data, development of model, the test of usage and estimation of model for administration and management of education for development of innovation of learners in digital period for private institutions of Udon Thani province by 4 periods of research as 1. a study of fundamental data from data tellers as administrators and teachers for 110 persons and wise persons for 15 persons, 2. Development of model for data tellers from specialists for 9 persons, 3. The test for model from administrators for 55 persons and teachers for 55 personas and learners 1,100 persons and 4. The estimation of model for data tellers from administrators for 55 persons and teachers for 55 persons and learners for 110 persons. The instruments using for the research included questionnaires, record model and estimation. The statistics included percentage, mean and standard deviation. The hypothesis testing used t-test. The results of findings were as follows: 1. For overall of the results on study the current condition for educational administration and management for development of innovation of learners in digital period for private institutions of Udon Thani province were in high level and the condition of needs was in high level for overall. 2. The results of estimation for model and handbook for usage the model on educational administration and management for development of innovation of learners in digital period for private institutions of Udon Thani province were in appropriate high level for overall. 3. The results of estimation for administration and management of administrators on development of model for educational administration and management on development of innovation of learners in digital period for private instructions in Udon Thani province for before development was in high level for overall and after development were in high level for overall as the same. 4. The results of estimation for learning management of teachers on development of model for administration and management on development of innovation of learners in digital period for before development was in high level for overall and after development were in high level for overall as the same. 5. The results of estimation for learning of learners on development of model for educational administration and management for development of innovation of learners in digital period for before development was in high level for overall and after development were in high level for overall as the same. 6. The results of estimation for capacity for innovation of learners before development was in high level for overall and after development were in high lever for overall as the same. 7. The results of estimation of satisfaction towards operation by the model of educational administration and management for development of innovation on learners in digital period were in high level for overall. 8. The results of estimation of possibility and utility for the model of administration and managements for education on development of innovation of learners in digital period were in high level for overall.